INTEGRITAS TEKNOLOGI DALAM STUDI QUR’AN: DAMPAK NEGATIF KEBIASAAN GEN Z MENGGUNAKAN HANDPHONE MELALUI APLIKASI MUSLIM PRO DALAM MEMBACA AL- QUR’AN - Fujianti, Indah (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2025)
Abstract This study aims to provide a view of the negative impacts of Gen Z's habit of using mobile phones when reading the Qur'an. The possible impacts can be used as a reference for finding solutions so that technology can continue to be used and coexist with the Qur'an but does not have a negative impact on the Islamic generation. The method used by the author is the observation method by directly researching the object and observing the phenomena that occur in the field. The data collection technique in this study is the direct object interview technique, namely in this case students of STAI Haji Agus Salim Bekasi. The results of this study, researchers found facts, one of which is that 50% of students use mobile phones, especially the Qur'an application, for the needs of memorizing the Qur'an to make it easier, they still use the physical Qur'an in doing tadarus. The author hopes that with this article, users of mobile phones or Qur'an applications can pay attention to the negative impacts of using the Qur'an application alone without using the physical Qur'an.